Recommendation of Yogyakarta tourism based on simple additive weighting under fuzziness - Utomo, Eko Yunanto (Journal of Soft Computing Exploration, 2021)
For tourists who do not understand the situation or the desired tourist attraction, they can choose tour and travel services. Tour and travel provides a choice of tour packages with various variations. Determining the right tour and travel package and agency can benefit tourists, both in terms of financial and vacation quality. The data used in this study were obtained from several Tour and Travel agents. There are several variables used, namely the price of the package, the number of participants, and the number of facilities obtained. The method used in this study combines the Triangular Fuzzy Number (TFN) and the Simple Additive Weighting (SAW) method. The purpose of this study is to help tourists determine the most profitable or best packages. The results of this study obtained the best 2 packages recommended for tourists to choose.